The New Theory of Legislation - Arias-Schreiber, Félix (2015)
This article discusses on the new theory of legislation. It is presented considering its antecedents, and its treatment from sociology of law to the current state of its development. It is make emphasis on the interdisciplinary nature of this theory for a better understanding of the legislative process, without failing to acknowledge the importance of its legal status.